Intrathecal Tramadol for prevention of shivering in Anorectal surgeries under Sub arachnoid anaesthesia - Sarvesh Jain; Rohit Dushyant; K K Arora (International Journal of Medical Research and Review, 2014)
Introduction: Shivering is very common problem during Sub arachnoid block (SAB), also known as Spinal anaesthesia. It can be prevented by intrathecal opioid injection.Material and method: In our study we have included 50 patients scheduled for anorectal surgery. They all were given spinal anaesthesia with bupivacaine 12.5 mg along with injection Tramadol 10 mg and watched for initial 4 hour.Result: 3 out of 50 patients showed shivering in treatment group who have received injection Tramadol.Discussion: Probable mechanism of action is its activity at mu receptor and serotonin and nor epinephrine reuptake inhibitionConclusion: Intrathecal Tramadol in dose of 10 mg prevents shivering in most of the patients. It can safely be used for prevention of shivering without significant side effect.